PENGARUH SPIP DAN TRANSPARANSI TERHADAP AKUNTABILITAS KINERJA PEMERINTAH DAERAH: APAKAH CHANGE MANAGEMENT DAN PERGANTIAN KEPEMIMPINAN MAMPU MEMODERASI? - Puspita Sari, Selly; Fuadi, Fauzan (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
Local government performance accountability to stakeholders through performance accountability is still weak due to a lack of commitment and unsynchronised regulations. This study examined the effect of the Government's Internal Control System (SPIP) and transparency on local government performance accountability with change management and leadership turnover as moderators. This study used 65 respondents of Pringsewu Regency government employees who prepared the Government Agency Performance Accountability System (SAKIP). The analysis was conducted using a structural model using the SEM-PLS method. The results of this study indicate that SPIP has a positive effect on performance accountability, and change management has been proven to strengthen its influence on performance accountability. In addition, leadership change strengthens the influence of transparency on local government performance accountability. The results of this study provide important insights for local governments in improving government performance accountability.